(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
There is a serious dilemma about whether to respect the international norm, which prohibits the use of force in the internal affairs in the form of intervention or to intervene when it comes to open and gross violations of the international humanitarian law. The dilemma is expressed as a conflict between legitimacy and legality. The author investigates the relation between legality and legitimacy, i.e. the conditions in which legitimacy has a priority over legality. According to the principle of legality, based on purely legal grounds, intervention must not be carried out unless all legal conditions are met. But, according to the principle of legitimacy, which is mainly based on political motives and moral considerations, the implementation of intervention is justified. Legality is determined by precisely defined legal norms, and legitimacy is the result of extensive comprehension of law and the result of doctrinal disputes and public opinions. The possibilities and acceptance of the fact that humanitarian intervention has been used as a justification for illegal military intervention, reconsider the moral and the legal support for humanitarian intervention. The overall situation is additionally blurred by the view of legitimacy, that is, the international legal status of the force that implements or calls for humanitarian intervention. There is still a division of the views about whether the humanitarian action carried out in the form of violent intervention or unilateral intervention is beyond the legally accepted UN Charter?!